Marine Catch Analysis For The Economy Of Coastal Communities - Muhammad Sutrisno; Muhammad Rizky Ramadhan; Mhd. Sahrizal; M. Salman Al Parisi; M. Hanapi (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2023)
Analysis of marine catches for the economy of coastal communities is an important thing to do. This is because marine catches are one of the main sources of livelihood for coastal communities. Marine catches can make a significant contribution to the economy of coastal communities, either directly or indirectly. Directly, marine catches can provide income for fishermen and other coastal communities involved in fishing activities. This income can be used to meet daily living needs, such as for food, clothing, health, education, and so on. Indirectly, marine catches can contribute to the economy of coastal communities through various other economic activities, such as trade, processing, and tourism. These activities can absorb labor and increase the income of coastal communities. Based on the results of the analysis, it is known that marine catches have an important role in the economy of coastal communities. Therefore, efforts need to be made to increase marine catches, both in quantity and quality. These efforts can be done through various means, such as improving fishing technology, sustainable fish resource management, and improving fishermen's skills.